In Vitro Microleakage Comparison of Flowable Nanocomposites and Conventional Materials Used in Pit and Fissure Sealant Therapy - Sara Arastoo; Azam Behboudi; Vahid Rakhshan (Tehran University of Medical Sciences, 2019)
Objectives: Pit and fissure sealants are recognized as an effective preventive  approach in pediatric dentistry. Composite resin is the most commonly used sealant material. Adding nanoparticles to composite resin could result in production of flowable composite with higher mechanical properties and better flowability than previous sealants. This study aimed to compare the microleakage of a flowable nanocomposite and materials conventionally used as pit and fissure sealants. Materials and Methods: A total of 185 extracted mandibular third molar teeth were selected and randomly divided into 5 groups (n=36): flowable nanocomposite, flowable composite, filled sealants, nano-filled sealants, and unfilled sealants. Five teeth were reserved for examination under a scanning electron microscope (SEM). The samples were thermocycled (5-55°C, 1-minute dwell time) for 1000 cycles and immersed in 0.2% fuchsine solution for 24 hours. Teeth were sectioned buccolingually. Microleakage was assessed qualitatively and quantitatively by means of dye penetration and SEM. Data were analyzed using chi-square, Kruskal-Wallis, and Bonferroni-corrected Mann-Whitney U tests. Results: Qualitative microleakage assessment showed that flowable composite and nanofilled flowable composite had almost no microleakage (P<0.001). Regarding quantitative scores, the nanofilled flowable composite and unfilled fissure sealant showed the lowest and the highest rate of microleakage, respectively. No statistically significant difference was found between the two flowable composites (P=0.317). Filled resin-based sealant had significantly lower microleakage than unfilled resin-based sealant (P<0.001). Conclusion: Use of flowable and nanofilled flowable composites (but not unfilled resin-based fissure sealant) is recommended for sealing of pits and fissures of molars